Bibliometric analysis of research on retinoic acid in the field of kidney disorders - Liu, Yu; Sun, Dongxuan; Huang, Youqun; Shen, Yuli; Chen, Tong; Chen, Wenya; Zhu, Liangjun; Wang, Fang; Hong, Guoai; Luo, Yuechan; Long, Siyu; Zou, Hequn (Frontiers in Pharmacology, 2024)
Retinoic acid is an active metabolite with significant physiological functions in human development, immunity, vision, and skin health. In recent years, research on retinoic acid in the field of kidney disorders has been increasing gradually. Yet, there is a lack of systematic bibliometric analysis of retinoic acid research in the kidney domain. This study included 1,368 articles published between 1998 and 2023 on treating kidney diseases with retinoic acid. Using the bibliometric analysis software VOSviewer and CiteSpace, we analyzed data on publication trends, contributing countries and institutions, journals and cocited journals, authors and cocited authors, cocited references, research hotspots, and frontiers. On the basis of the results of the bibliometric analysis, we identified the research efforts and their developmental trends, providing the groundwork for future research on retinoic acid.